Clinical Outcome in Acute Ischemic Stroke Patients With Microbleeds After Thrombolytic Therapy: A Meta-Analysis. Issue 52 (December 2015) - Cai, Jing; Fu, Jingjing; Yan, Shenqiang; Hu, Haitao; Lin, Chen
Abstract : Abstract: It remains unclear whether preexisting cerebral microbleeds (CMBs) increase the risks of worse functional outcome after thrombolytic therapy. We performed a systematic review and meta-analysis to assess the risk of unfavorable outcome in patients with acute ischemic stroke and CMBs. We searched EMBASE, PubMed, and Web of Science for relevant studies assessing functional outcome in the patients with CMBs following thrombolytic therapy. Fixed-effects and random-effects models were performed. Five eligible studies including 1974 patients were pooled in meta-analysis. The prevalence of CMBs was 24.3%. The pooled analysis demonstrates odds ratio for preexisting CMBs and the achievement of favorable outcome to be 0.69 (95% CI 0.56–0.86; P  = 0.001) with no evidence of statistical heterogeneity (I 2  = 46.7%, P  = 0.112). Our meta-analysis of available published data demonstrates an increased risk of worse functional outcome after thrombolytic therapy for acute ischemic stroke in patients with pre-existing CMBs. Future studies are needed to determine whether the risk outweigh the expected benefit of reperfusion therapies.